2013
DOI: 10.1182/blood-2012-10-462358
|View full text |Cite
|
Sign up to set email alerts
|

Independent prognostic value of BCR-ABL1-like signature and IKZF1 deletion, but not high CRLF2 expression, in children with B-cell precursor ALL

Abstract: Key Points• BCR-ABL1-like signature and IKZF1 deletions are clinically important to identify high-risk acute lymphoblastic patients.Most relapses in childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL) are not predicted using current prognostic features. Here, we determined the cooccurrence and independent prognostic relevance of 3 recently identified prognostic features: BCR-ABL1-like gene signature, deletions in IKZF1, and high CRLF2 messenger RNA expression (CRLF2-high). These features were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
251
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(273 citation statements)
references
References 40 publications
19
251
2
1
Order By: Relevance
“…Indeed, about two-thirds of kinase-driven ALLs, commonly called "Philadelphia like" (Ph-like) ALLs, demonstrate activation of this pathway similarly to DS-ALL (11,12). The prognosis of these leukemias is worse (11)(12)(13)(14)(15)(16)(17)(18)(19) and a clinical trial incorporating ruxolitinib into the chemotherapy backbone for newly diagnosed patients has been recently opened (NCT02723994).…”
Section: Significancementioning
confidence: 99%
“…Indeed, about two-thirds of kinase-driven ALLs, commonly called "Philadelphia like" (Ph-like) ALLs, demonstrate activation of this pathway similarly to DS-ALL (11,12). The prognosis of these leukemias is worse (11)(12)(13)(14)(15)(16)(17)(18)(19) and a clinical trial incorporating ruxolitinib into the chemotherapy backbone for newly diagnosed patients has been recently opened (NCT02723994).…”
Section: Significancementioning
confidence: 99%
“…This signature comparison study comprised children with newly diagnosed BCP-ALL negative for the known aberrations BCR-ABL1, ETV6-RUNX1, MLL rearrangement, TCF3 rearrangement, and high-hyperdiploidy in consecutive Dutch Childhood Oncology Group (DCOG) and German Cooperative ALL trials (146 cases), 2,6 and the P9906 study of the US Childhood Oncology Group (COG) (143 cases). 2,4-6 Molecular aberrations were determined as described in the Online Supplementary Methods.…”
Section: 6mentioning
confidence: 99%
“…4,5 The signature developed by Den Boer et al is based on hierarchical clustering (HC) of 110 gene probe sets identified to predict the major pediatric ALL subtypes (T-cell ALL, ETV6-RUNX1, high-hyperdiploidy, TCF3 or MLL-rearranged, BCR-ABL1). 2,6 This group of BCR-ABL1-like patients had frequent deletions in B-cell development genes (e.g. IKZF1), dic(9;20), and intrachromosomal amplification of chromosome 21 (iAMP21).…”
mentioning
confidence: 99%
“…Ph-like ALL is associated with high-risk clinical features, a poor response to induction chemotherapy, elevated minimal residual disease (MRD) levels, and/or poor survival. 7,14,22,30,51,52 Several observations indicate that tyrosine kinase inhibitors (TKIs) may be effective in Ph-like ALL. Kinase fusions and sequence mutations confer cytokine-independent proliferation in mouse pre-B-cell lines that is abrogated by tyrosine kinase inhibitors (TKIs), ABL1 inhibitors such as imatinib and dasatinib for ABL-class fusions, and JAK2 inhibitors for JAK-STAT-activating alterations.…”
mentioning
confidence: 99%